Formulasi Dan Uji Aktivitas Antibakteri Sediaan Krim Ekstrak Etanol Kulit Buah Manggis (Garcinia Mangostana Linn.) Terhadap Bakteri Propionibacterium Acnes ATCC 1335 - Lydia Fitriana; Tiara Ajeng L; Anita Dwi Septiarini S; Danang Raharjo (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The skin is the widest organ that makes up the human body which is the outermost and covers the entire surface of the body. The outermost location causes the skin to receive stimulation for the first time such as touch stimulation, pain, or bad influences from outside. This causes the skin to stretch due to disease. One of the most common skin diseases suffered by people is acne. Acne occurs generally triggered by the bacterium Propionibacterium acnes (gram positive bacteria). Effective acne treatment can use antibiotics, but inappropriate use of antibiotics can lead to resistance. Therefore it is necessary to have alternative therapies from plants that have the potential as antibacterial. One of the natural ingredients from plants that have antibacterial properties is mangosteen (Garcinia mangostana Linn.)This research was conducted using a descriptive experimental method with the aim of knowing the presence of antibacterial activity in cream preparations of ethanol extract of mangosteen rind (Garcinia mangostana Linn.) against Propionibacterium acnes bacteria as seen from the inhibition of bacteria with varying concentrations of 10%, 15% and 25% by using paper disc diffusion method and solid liquid dilution method. The positive control used clindamycin cream and the negative control used 1% DMSO. Analysis of the diameter of the inhibition data was carried out using the One Way ANOVA test. The preparation formulation that has the largest diameter in the diffusion test is F3 with a concentration of 25% with an average inhibition of 6.36 in the medium category. The MIC and KBM values in the dilution method were at a concentration of 12.5%. The results of a normally distributed One Way ANOVA are measured with a value (P> 0.05). Mangosteen peel extract (Garcinia mangostana Linn.) has antibacterial activity against Propionibacterium acnes bacteria.